Analysis Of Services Of Bintang Kecil Community Reading Park In Batu Palano, West Sumatra Towards Library Services In Facing The Covid-19 Pandemic - Ajri Rhaysa Maulina; Sukaesih -; Evi Nursanti Rukmana; Samson CMS - (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2021)
The prolonged Covid-19 pandemic during 2020 made all activities blocked, delayed, and even stopped. The people of Batu Palano, Sungai Pua District, Agam Regency, West Sumatra, have also felt the impact of the Covid-19 pandemic by limiting their activities and direct contact with people (physical distancing). One of the restricted activities is online school learning for the kindergarten to college level. Online-based school learning does not allow all regions to access it every day. This problem also affects school children in Batu Palano. Most junior high school and elementary school children in Batu Palano do not have gadgets to carry out online learning. So that Bintang Kecil Reading Park in Batu Palano becomes an oasis for school children in accessing its collections to support their online learning activities. This study analyzes the relationship between community reading park Bintang Kecil and library services, whether they have the same services even though they have different titles, and how Bintang Kecil community reading park survives in the Covid-19 pandemic situation. Implementing the management of the Bintang Kecil Reading Park really implements the role of the librarian in serving the users in it. The establishment of the Bintang Kecil Reading Park in Batu Palano Village can be the first step to increase its collection so that in the future it can develop into a village library where not only school children have access to information, but can also provide collection sources. To other people in Batu Palano Village.